Peningkatan Kemampuan Operasi Hitung Penjumlahan dan Pengurangan Dengan Media Konkret Pada Siswa Kelas 1 SD Negeri Bantarkawung 03 - Rizkiana, Alif (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The arithmetic operations of addition and subtraction are basic mathematics that must be learned since the 1st grade of elementary school to make it easier for students to do mathematics in advanced grades. In this research, the aim is to improve the ability to do arithmetic operations of addition and subtraction with concrete media for grade 1 students at SD Negeri Bantarkawung 03. Through classroom action research, the quality of learning can be improved because the teacher immediately knows what needs to be improved. The number of respondents studied in this study were all first grade elementary school students, totaling 22 students. This research was carried out in 2 cycles. Based on the description of the implementation of the action, the results of the research and discussion, data were obtained that there was an increase in the ability to do arithmetic addition and subtraction operations in each cycle. It can be seen from the application of the pre-cycle, that is, 40% has increased to 20%, so the total is 60% in the first cycle, then it has increased in the second cycle, which is an increase of 27%, the total increase is 87%. The conclusion is that using concrete objects media can improve the ability of addition and subtraction arithmetic operations in grade 1 students of SD Negeri Bantarkawung 03